The dual role of evo-devo mechanisms and the extended evolutionary synthesis - Folguera, Guillermo (2018)
The distinction between mechanisms that generate biological variation and mechanisms that modify it has been important in contemporary Biology, especially since the establishment of the Evolutionary Synthesis (ES) in the first part of the twentieth century. In the ES, and in its subsequent legacy to evolutionary biology, the focus was directed at mechanisms that modify biological variation. In recent years, evo-devo (Evolutionary Developmental Biology) emerged as an area of knowledge that proposes to extend the ES in many forms. In this sense, given that evo-devo integrates different areas of Biology, different types of mechanisms can be found. In order to understand evo-devo mechanisms, as well as its relation with the ES, we analyzed the role that evo-devo mechanisms play with respect to biological variation. The main question in our analysis was: do evo-devo mechanisms have a function of generators and/or modifiers of biological variation? We focused on three evo-devo mechanisms: environmental induction, hypervariability/somatic selection and developmental bias. Our analysis showed a different characterization of the action of evo-devo mechanisms. This heterogeneity in the role of evo-devo mechanisms shows that, in general, the distinction is maintained but there is a mechanism that presents a dual role. Our analysis indicates that, at least with respect to mechanisms, evo-devo extends and departs from what was proposed in the evolutionary synthesis.